COMPARISON OF IRON STATUS AND INSULIN RESISTANCE BETWEEN NON-DIABETIC OFFSPRING OF TYPE 2 DIABETICS AND NON-DIABETIC OFFSPRING OF NON-DIABETICS - Zafar, Uzma; Qureshi, Hamid Javaid; Imran, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Insulin resistance is positively correlated with body iron. It is unclear whether iron is a cause or an outcome of insulin resistance. Insulin resistance precedes type 2 diabetes mellitus. Offspring of type 2 diabetics are insulin resistant as compared to those of the non-diabetics. The present study was designed to compare and correlate insulin resistance with iron parameters (including serum ferritin, transferrin saturation and blood haemoglobin) in non-diabetic offspring of type 2 diabetics and non-diabetic offspring of non-diabetics. Methods: It was a cross-sectional study, conducted on one hundred and twenty male subjects 20-40 years of age. They were divided into two groups, each group having 60 subjects. Group A included non-diabetic offspring of type 2 diabetics, while Group B included non-diabetic offspring of non-diabetics. Fasting blood sample was taken and examined for glucose, haemoglobin, insulin, iron, TIBC and ferritin. Data was analysed by SPSS-17. Results: Insulin resistance and iron parameters were significantly higher (p<0.05) in non-diabetic offspring of type 2 diabetics as compared to those of the non-diabetics. There was significant positive correlation (p=0.027) between insulin resistance and serum iron in non-diabetic offspring of type 2 diabetics. There was also significant positive correlation between insulin resistance and serum iron, transferrin saturation and haemoglobin in non-diabetic offspring of non-diabetics. Conclusion: Non-diabetic offspring of type 2 diabetics have iron load and insulin resistance, that predispose them to the development of type 2 diabetes. Keywords: Insulin resistance, offspring of type 2 diabetics, serum ferritin, transferrin saturation